PENGARUH POC KULIT NANAS DENGAN AZOLLA PINNATA DAN NPK TERHADAP PERTUMBUHAN SERTA PRODUKSI TANAMAN TERUNG TELUNJUK - Agung Dwi Pramana; Desrihastuti; Adelina Maryanti; Saripah Ulpah (UIR Press, 2024)
Finger eggplant is a valuable fruit vegetable that is highly sought by the Indonesian population. Unfortunately, its production has been declining annually due to diminishing soil fertility. To address this issue, it is essential to enhance the soil's physical, chemical, and biological properties to boost both finger eggplant production and soil productivity. This can be achieved by applying liquid organic fertilizer made from pineapple skin, combined with Azolla pinnata and NPK fertilizer. The objective of this study is to evaluate the interaction and individual effects of pineapple skin liquid organic fertilizer (POC) with Azolla pinnata and NPK on the growth and yield of finger eggplant (Solanum melongena L.). The research took place at the Experimental Farm of the Faculty of Agriculture at Riau Islamic University in Pekanbaru, running from June to September 2024. A factorial Completely Randomized Design (CRD) was employed, featuring two factors. The first factor involved varying levels of pineapple skin POC with Azolla pinnata, specifically 0, 50, 150, and 250 ml per liter of water. The second factor consisted of four levels of NPK fertilizer: 0, 10, 20, and 30 g per plant, resulting in 16 treatment combinations with three replications, yielding a total of 48 experimental units. The parameters measured included plant height, flowering age, harvest age, number of fruits per plant, total fruit weight per plant, weight per fruit, and number of remaining fruits. The collected data were analyzed statistically, followed by further BNJ tests at the 5% significance level. The findings revealed that the interaction between pineapple skin POC, Azolla pinnata, and NPK fertilizer (15:9:20) significantly influenced several parameters, including plant height, flowering age, harvest age, number of fruits per plant, total fruit weight per plant, weight per fruit, and number of remaining fruits. The optimal treatment was identified as the combination of pineapple skin POC with Azolla pinnata at 250 ml per liter of water and NPK fertilizer at 30 g per plant. In conclusion, the study indicates that using pineapple skin POC combined with Azolla pinnata at a concentration of 250 ml per liter of water, along with 30 g of NPK fertilizer per plant, can effectively enhance finger eggplant production. Additionally, it is recommended to increase the phosphorus content in the NPK fertilizer for more optimal growth of the eggplant plants.